2014
DOI: 10.4028/www.scientific.net/amm.553.305
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) Based Finite Element Modeling for Analyzing the Influence of Material Properties on Menisci Responses

Abstract: To investigate the importance of the meniscal non-linear behaviour on knee joint finite element analysis (FEA) study, the aim of this study was to compare linear elastic and nonlinear hyperelastic material models on the pressure distribution of meniscus. For this purpose, a 3D finite element (FE) knee model of a healthy living subject was constructed from magnetic resonance imaging (MRI) to simulate contact pressure under axial compressive loading. Differences in meniscal contact pressures were observed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Table 2 presents a comparison between our results and results of previous FEA studies. Similar to other studies, 62,87,88 the cartilage stress in the medial compartment was found to be larger than that in the lateral compartment, which corresponds to clinical findings showing a greater prevalence of medial OA. 92 Hence, the consistency between the results as to shear and Von Mises stresses in this work and the ones in the literature demonstrated that the current FE model is able to generate truthful results.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Table 2 presents a comparison between our results and results of previous FEA studies. Similar to other studies, 62,87,88 the cartilage stress in the medial compartment was found to be larger than that in the lateral compartment, which corresponds to clinical findings showing a greater prevalence of medial OA. 92 Hence, the consistency between the results as to shear and Von Mises stresses in this work and the ones in the literature demonstrated that the current FE model is able to generate truthful results.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies 4854,57 have assumed the femur and tibia as rigid bodies because of their relatively high density and Young’s modulus compared to the cartilage and menisci in the knee joint. On the other hand, previous FEA studies 56,5862 did not take into account the difference between cancellous and cortical bone and considered the whole bony structure of the knee joint as cortical bone. For example, Guess et al 56 developed the dynamic 3D anatomical knee joint models with sufficient computational competence for human movement simulation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid elements are mainly used when Poisson's ratio exceeds 0.48 and the material behaviour approximates nearly incompressible. 25 The element and material properties 17,18,26,27 for each component modelled are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%